2017
DOI: 10.1016/j.ebiom.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen (HLA) and Gulf War Illness (GWI): HLA-DRB1*13:02 Spares Subcortical Atrophy in Gulf War Veterans

Abstract: BackgroundGulf War Illness (GWI) is a multisystem disorder that has affected a substantial number of veterans who served in the 1990–91 Gulf War. The brain is prominently affected, as manifested by the presence of neurological, cognitive and mood symptoms. We reported previously on the protective role of six Human Leukocyte Antigen (HLA) alleles in GWI (Georgopoulos et al., 2016) and their association with regional brain function (James et al., 2016). More recently, we reported on the presence of subcortical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 30 publications
4
62
0
Order By: Relevance
“…Successful elimination of such antigens depends on a match between a specific antigen and one's HLA composition. A mismatch, on the other hand, prevents elimination of the antigen, and the “persistent antigen” [ 16 ] may lead to inflammation, cell damage, autoimmunity [ 40 ], and atrophy [ 14 ]. Evidence suggests that antigens related to several common illnesses including influenza A, hepatitis B and C, and herpes virus bind to HLA DRB1*13:02 and HLA DRB1*13:01 [ 41 ], thereby facilitating elimination of those antigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful elimination of such antigens depends on a match between a specific antigen and one's HLA composition. A mismatch, on the other hand, prevents elimination of the antigen, and the “persistent antigen” [ 16 ] may lead to inflammation, cell damage, autoimmunity [ 40 ], and atrophy [ 14 ]. Evidence suggests that antigens related to several common illnesses including influenza A, hepatitis B and C, and herpes virus bind to HLA DRB1*13:02 and HLA DRB1*13:01 [ 41 ], thereby facilitating elimination of those antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, neuroprotection by DRB1*13 could be exerted by (a) eliminating persistent neurotoxic antigens [ 16 ], (b) limiting the presence of cathepsin S, a known endogenous harmful substance in brain aging [ 48 ], to which DRB1*13:02 binds with high, and DRB1*13:01 with lower, affinity [ 49 ], and (c) limiting the presence of amyloid A beta by facilitating the production of autoantibodies against it [ 47 ]. Concerning apoE, the detrimental effects of E4 and various mechanisms of action have been well established and investigated, as reviewed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with MDD have an overall decreased volume of grey matter (Matsuo et al, 2017), and more specifically regions of the brain associated with emotional processing such as the area 9 of the dorsolateral pre-frontal cortex (Cotter et al, 2002) and the amygdala (Hamidi et al, 2004). Furthermore, in subjects with Gulf War Veterans Illness (GWVI), a set of disorders specific to veterans of the Gulf War and characterized by fatigue, memory impairment, and depression, there was an established increase of subcortical atrophy, which was increased in veterans who lacked the DRB1*13:02 HLA Allele (James et al, 2017). This MHCII allele is known to confer protection against auto inflammatory conditions such as rheumatoid arthritis (Feitsma et al, 2008) and provides an interesting link between autoinflammatory conditions and genetic contributions to pathogen recognition by the innate immune system.…”
Section: Nlrp3 Inflammasome Cytokines and Their Effectsmentioning
confidence: 99%
“…Furthermore, the observation that a subset of veterans developed GWI, while nearly all soldiers were likely exposed to some combination of toxicants in theater, strongly supports the hypothesis that veterans with GWI may harbor some specific genetic-susceptibility. In the most recent publication from the Georgopoulos group, James et al (2017) expand upon several of their previous studies verifying the protective role of HLA alleles related to brain function ( Georgopoulos et al, 2015 , James et al, 2016 ) in the observed subcortical brain atrophy associated with GWI ( Christova et al, 2017 ). Here, James et al’s (2017) evaluation of subcortical brain volumes in Gulf War veterans supported the suspected protective effect of the HLA class II allele DRB1*13:02 by finding a significantly higher subcortical volume in carriers of this allele.…”
mentioning
confidence: 86%